Análisis socioeconómico de los pequeños productores de arroz en el recinto Clarisa, cantón Daule, Ecuador - Barzola Consuegra, María Cristina (2022)
In line with the evolution of theories of development in relation to economic activity, which focus the analysis on the citizen and take into account local characteristics, the present study followed the objective of analyzing the socioeconomic conditions of small rice producers in the Clarisa enclosure, Daule canton, Ecuador. The country is a notable consumer and producer of this grass; therefore the productive work of the farmer is eminently important for economic growth; hence the relevance of the study that is also supported by the widespread theory and the legal basis of regional regulations as well as the Constitution of the Republic of Ecuador (2008) and the corresponding laws. Methodologically, we proceeded with a mixed approach and type of descriptive research. The statistical techniques of the survey and the interview were applied, the results of which defined contrasting realities of the social situation of small rice producers, in terms of the low level of education and medical care, and negligible living conditions in general. In coherence, the economic difficulties it faces due to having limited areas of land and especially the high cost of inputs, among others, are serious. Likewise, the SWOT matrix was determined that made it possible to project the offensive, defensive, survival and adaptive strategies, with the consideration of the implementation of the offensive strategy since the strengths and opportunities are potentially usable, for the improvement of the socioeconomic conditions of small rice producers and the sector in general.